Kinetic study of hydrolysis of ethyl acetate using caustic soda - Ghobashy, Mostafa; Gadallah, Mamdouh; T.El-Idreesy, Tamer; A.Sadek, M.; A.Elazab, Hany (International Journal of Engineering and Technology, 2018)
We report here, the hydrolysis of ethyl acetate by using caustic soda which is followed by means of conductance measurements which is widely used in chemical industry. The main aim of this research is to study the parameters of production of ethyl acetate by chemical reaction kinetics using an anion ion-exchange acting as a catalyst and acid-base titrations. The reaction of ethyl acetate and sodium hydroxide (caustic-soda) is done in a plug-flow reactor (steady-state tubular reactor) under the effect of different parameters including temperature, concentration and flow-rate, which allows the determination of activation energy and rate constants, due to large number of experiments. Factorial design method is used for the calculations of the experiment. It was determined that the order of the reaction is a second-order reaction.Â Â